Educational Technology for Digital Transformation of Higher Education Institutions into Entrepreneurial Universities - Wijayanto Aripradono, Heru; Nursyamsi, Idayanti; Wahab, Abdul; Sultan, Zulkifli (Indonesian Association for Public Administration, 2024)
Digital technology is transforming higher education institutions into entrepreneurial universities, which, in turn, supports economic development and knowledge generation. The integration of education technology enhances access, equity, inclusion, and the quality of learning experiences. This research aims to uncover how educational technology promotes digital transformation in Indonesia's higher education, fosters an entrepreneurial mindset, and contributes to social and economic growth. This study uses a quantitative approach with a survey method, with the data collected using purposive sampling. The questionnaire was designed to represent the indicators set in the variables, and the results were analyzed using the structural equation modeling (SEM) method. This study analyzes 45 universities aiming to become entrepreneurial institutions, with 155 respondents filling out the questionnaire. The integration of educational technology and digital transformation in higher education has significant implications, affecting teaching methods, administrative efficiency, and the educational environment. The entrepreneurial university model emphasizes collaboration and responsiveness to market needs, preparing graduates for a competitive job market. This shift requires a reassessment of traditional teaching methods and a shift in mission. The successful integration requires strategic planning, transformational leadership, investment in digital infrastructure, and fostering a culture of innovation.